Assessing performance variability of ground handlers to comply with airport quality standards. (October 2016) - Patriarca, Riccardo; Di Gravio, Giulio; Costantino, Francesco
Abstract: The increasing competition in the air transport industry continuously pushes ground handlers to improve their performance. Recent European regulations prescribe that the managing body of large European airports (more than 5, 000, 000 passengers/year or 100, 000 tonnes/year of freight) have to define quality standards of service level for ground handler operations. In case a handler fails to meet these minimum requirements, the airport has to report it these irregularities, potentially imposing a fine or even suspending, partly or fully, the handler's services. As always recognized by the passengers, one of the most critical quality standards is the baggage handling waiting time. This paper defines a methodology to assess whether the handler fits the requirements of first baggage delivery for both the overall process and the specific segments (flight, conveyor belt, departing airport, day of the week, etc.). The methodology, analysing the performance by a two-dimensional perspective (structure and frequency), will help the decision makers in defining mitigating actions to take the performance under statistical control, respecting the requirements and preventing any drift. Highlights: The paper defines a methodology to assess service level of ground handlers. The assessment considers both the overall process and its specific segments. A two-dimensional perspective, with structure and frequency, analyses the first baggage delivery. The methodology helps the decision maker to define mitigating actions and respect the airport requirements. A real airport baggage handling case study shows the benefits and managerial implication.